Undergraduate Education for Public Health in the United States - David Thomas Dyjack (Frontiers Research Topics, 2015)
Undergraduate programs in public health are growing rapidly. At colleges and universities throughout the United States, both the number of programs and the number of students have expanded greatly in the past decade. In response to this trend, the Council for Education of Public Health (CEPH) has begun to accredit undergraduate public health programs, with the first programs approved in 2014. Around the country programs exhibit wide variation, from concentrations in liberal arts colleges to pre-clinical foundations at doctorate-granting universities to undergraduate programs in accredited schools of public health. Faculty, both new and seasoned, are fully aware of the need to integrate undergraduate education in public health with graduate education-but the roadmaps of exactly how to do so are still nascent. The purpose of this Research Topic is to gather articles describing this variation, with the intent that the collective body of work will facilitate analysis and discussion of what makes a quality education and builds a competent workforce.